2019
DOI: 10.1117/1.jbo.24.4.046005
|View full text |Cite
|
Sign up to set email alerts
|

Optimization-based vessel segmentation pipeline for robust quantification of capillary networks in skin with optical coherence tomography angiography

Abstract: Optical coherence tomography angiography (OCTA) provides in-vivo images of microvascular perfusion in high resolution. For its application to basic and clinical research, an automatic and robust quantification of the capillary architecture is mandatory. Only this makes it possible to reliably analyze large amounts of image data, to establish biomarkers, and to monitor disease developments. However, due to its optical properties, OCTA images of skin often suffer from a poor signal-to-noise ratio and contain ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…2 ) captured the baseline perfusion of the microvascular network. The microvasculature was automatically segmented and analyzed by quantifying the vessel density (VD), length of the vascular network (LVN), and number of branch points (NBP) 32 . At the peak of reactive hyperemia perfusion (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ) captured the baseline perfusion of the microvascular network. The microvasculature was automatically segmented and analyzed by quantifying the vessel density (VD), length of the vascular network (LVN), and number of branch points (NBP) 32 . At the peak of reactive hyperemia perfusion (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…All data sets were deidentified and automatically segmented vessels (Fig. 2 ) were analyzed by various quantitative metrics described in detail in earlier works 17 , 32 . In summary, the vessel density (VD) is based on the area of segmented vessels (red pixels) as a percentage of the entire image (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Other works have employed a Frangi filter to improve visibility of vessels in OCTA images of the retina [ 49 ], choroid [ 67 ], and skin [ 41 ]. Despite its widespread use, the Frangi filter has also been criticized in some studies for introducing errors in the vessel architecture, either by missing vessels rendered in the image with low SNR or generating spurious vessels depending on the structure of the background noise [ 68 , 69 ]. Even using the multiscale Frangi filter approach, it has been shown that the results are highly dependent on the range of vessel sizes within the image [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Motion artifacts are a main limiting factor in any segmentation-based analysis because the algorithm does not differentiate artifacts from vessels. Casper et al have recently proposed a segmentation technique which incorporates a refinement step to help correct for defocus and blurring caused by motion, which may prove helpful [ 69 ]. In any case, if motion artifact exceeds a certain level (such as the example in Fig 8A and 8B ), there is no choice but to exclude the images from analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that the presence of skin cancers often coincides with an abnormal proliferation of the surrounding blood vessel system [ 4 , 17 , 18 ], which delivers oxygen and nutrients that support the growth of the malignancies. FF-OCT provides the capability of resolving vessels and capillaries in high-resolution images [ 14 , 19 , 20 ], which could help physicians track the maturity of tumors and the effect of drug delivery, allowing them to examine the evolution of the nearby angiogenesis. Past studies [ 4 , 21 , 22 ] have also demonstrated that inhibiting angiogenesis is a viable approach for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%